Association of red blood cell distribution width with presence and severity of rheumatic mitral valve stenosis - Mehmet Kadri Akboga; Adnan Abacı; Uğur Canpolat; Cağrı Yayla; Asife Sahinarslan; Kadri Açıkgöz; Serkan Çay; Serkan Topaloğlu; Dursun Aras; Sinan Aydoğdu (KARE Publishing, 2015)
Objective: As an indicator of variability in circulating erythrocyte size, red cell distribution width (RDW) is linked to chronic inflammation. The association of rheumatic heart valve stenosis and inflammation is also well-known. This study aimed to assess the relationship between RDW and presence and severity of rheumatic mitral valve stenosis (RMVS). Methods: A total of 417 consecutive patients with RMVS, and 81 age- and -gender matched healthy control subjects were included in the study between February 2009 and April 2014. Transthoracic echocardiography and demographic characteristics were recorded for all participants. Results: Baseline characteristics were similar in the two groups. However, median RDW was significantly higher in patients with RMVS compared to control group (14.4% [11.3- 19.6] vs. 13.6% [11.6-18.1], p<0.001). Additionally, both median C-reactive protein (CRP) and neutrophil-lymphocyte ratio (NLR) were also higher in the RMVS group; (6.1 [0.4-24.2] vs. 3.6 [0.3-15.3] mg/dl, p=0.001 for CRP, and 2.8 [0.4-10.6] vs. 2.1 [0.7-5.7], p<0.001 for NLR respectively). In regression analysis, RDW (OR: 1.504, p=0.005), CRP (OR: 1.139, p=0.008), NLR (OR: 1.528, p=0.018) and left atrial diameter (OR: 1.218, p<0.001) were found as independent predictors of the presence of RMVS. Furthermore, there was a significant positive correlation between CRP (r=0.140, p=0.007) and NLR levels (r=0.276, p<0.001) with RDW levels. Furthermore, we determined that RDW levels increased in parallel with severity of mitral stenosis (mild, moderate and severe) [13.7% (12.9-14.8), 14.4% (13.4-15.4), 14.8% (13.6-16.3), p<0.001, respectively]. Conclusion: The study demonstrated significantly higher RDW in patients with RMVS. Furthermore, RDW independently predicted the presence of RMVS. RDW is an easily available marker, and because of its correlation with common inflammatory indicators may also be a sign of chronic inflammatory continuum in patients with RMVS.